Mongolia : First and Second Reviews Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Mongolia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Mongolia's First and Second Reviews Under the Extended Fund Facility. Performance under the program thus far has been strong. Growth in 2017 is projected to reach 3.3 percent, considerably better than forecasted at the time of program approval. The combination of strong policy implementation and a supportive external environment has helped the authorities over-perform on all of the quantitative targets under the program. Performance on structural reforms has also been strong, notwithstanding the delays owing to the change in government in September 2017.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet